Samoa : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2003 Article IV Consultation highlights that Samoa's GDP growth slowed to 1.9 percent in 2001/02. This slowdown reflected mainly a steep decline in agriculture and a sharp contraction in construction activity. Although underlying inflation has remained low, headline inflation accelerated in this period, rising from 1.1 percent in 2000/01 to 9.8 percent in 2001/02 as a result of food supply shortages. Supervision in the financial sector has been enhanced by bringing all nonbank institutions under the supervisory regime of the central bank, and guidelines governing the supervision of these institutions are currently being developed.